Percutaneous Ablation for Small Renal Masses—Imaging Follow-Up - Iannuccilli, Jason D.; Grand, David J.; Dupuy, Damian E.; Mayo-Smith, William W. (Seminars in Interventional Radiology, 2014)
Image-guided percutaneous thermal ablation is a safe and effective nephron-sparing alternative to surgical resection for the treatment of small renal tumors. Assessment of treatment efficacy relies heavily on interval follow-up imaging after treatment. Contrast-enhanced computed tomography (CT) and magnetic resonance imaging (MRI) both play a pivotal role in evaluating the treatment zone, identifying residual tumor, and detecting early and delayed procedure-related complications. This article discusses a surveillance imaging protocol for patients who undergo percutaneous thermal ablation of renal tumors, and also illustrates the typical appearances of both successfully treated tumors and residual disease on contrast-enhanced CT or MRI. In addition, it discusses the imaging appearance of potential early and delayed treatment-related complications to facilitate their prompt detection and management.
Keywords: thermal ablation renal mass; ablation imaging follow-up